2021
DOI: 10.1073/pnas.2024824118
|View full text |Cite
|
Sign up to set email alerts
|

MAX mutant small-cell lung cancers exhibit impaired activities of MGA-dependent noncanonical polycomb repressive complex

Abstract: The MYC axis is disrupted in cancer, predominantly through activation of the MYC family oncogenes but also through inactivation of the MYC partner MAX or of the MAX partner MGA. MGA and MAX are also members of the polycomb repressive complex, ncPRC1.6. Here, we use genetically modified MAX-deficient small-cell lung cancer (SCLC) cells and carry out genome-wide and proteomics analyses to study the tumor suppressor function of MAX. We find that MAX mutant SCLCs have ASCL1 or NEUROD1 or combined ASCL1/NEUROD1 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Formal evidence for this hypothesis was provided in two SCLC mouse models, in which deletion of Max could either abrogate tumorigenesis if combined with a MYCL transgene, or favor it afterloss of the Rb1 and Trp53 tumors suppressors (Augert et al, 2020). Hence, in neuroendocrine tumors loss of Mga/Max/ PRC1.6 repressor function may be sufficient to bypass the requirement for Myc activity, as recently shown in Max-null human SCLC cell lines (Llabata et al, 2021). In other lineages, the essential role of Max as a Myc partner (Amati et al, 1993) may prevent its loss, but may still co-exist with its antagonist activities in complex with either Mga or Mxd/Mnt proteins.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Formal evidence for this hypothesis was provided in two SCLC mouse models, in which deletion of Max could either abrogate tumorigenesis if combined with a MYCL transgene, or favor it afterloss of the Rb1 and Trp53 tumors suppressors (Augert et al, 2020). Hence, in neuroendocrine tumors loss of Mga/Max/ PRC1.6 repressor function may be sufficient to bypass the requirement for Myc activity, as recently shown in Max-null human SCLC cell lines (Llabata et al, 2021). In other lineages, the essential role of Max as a Myc partner (Amati et al, 1993) may prevent its loss, but may still co-exist with its antagonist activities in complex with either Mga or Mxd/Mnt proteins.…”
Section: Introductionmentioning
confidence: 89%
“…First, genome sequencing studies revealed loss-of-function mutations in Mga in a wide variety of tumors (Schaub et al, 2018). Loss of Max was also observed, but appears to be restricted to neuroendocrine tumors, including pheochromocytoma (Comino-Mendez et al, 2011;Burnichon et al, 2012) and small-cell lung cancer (SCLC) (Romero et al, 2014;Llabata et al, 2021). In SCLC, mutations affecting the different network members (Max loss, Mga loss, Myc amplification) occur in a mutually exclusive manner, pointing to a common functional consequence (Romero et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MAX was found to be a tumor suppressor whose loss leads to derepression of serine and one-carbon pathway genes ( Augert et al 2020 ). Recent studies suggest that MAX-deficient SCLC is predominantly of the ASCL1 subtype and does not depend on any MYC family member ( Llabata et al 2021 ). These studies beg the question of whether a non-MYC family member state of SCLC is phenotypically and/or metabolically distinct from other molecular subsets.…”
Section: Heterogeneity In Therapeutic Responses: Ascl1 Vs Mycmentioning
confidence: 99%
“…MGA is a 350 KDa estimated weight protein composed by 3,065 amino acids [5, 6]. The detection of this protein is arduous, since it cannot be detected following the SWP even after its ectopic overexpression in a cancer cell line.…”
Section: Significant Changes For Large Protein Detectionmentioning
confidence: 99%
“…Here we describe a set of modifications from the Standard Work Procedure (SWP) of our laboratories to perform Western blots to detect either small or large proteins. These changes were used in different studies involving Small VCP Interacting Protein (SVIP) [4] and Max-Gene Associated Protein (MGA) [5, 6], and they led to overcome the technical issues related with the above-mentioned targets (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%